Development of a Spanish version of the parent attitudes about childhood vaccines survey. Issue 5 (4th May 2019) - Cunningham, Rachel M.; Kerr, G Brady; Orobio, Jessica; Munoz, Flor M.; Correa, Armando; Villafranco, Natalie; Monterrey, Ana C.; Opel, Douglas J.; Boom, Julie A.
ABSTRACT: The Parent Attitudes about Childhood Vaccines (PACV) survey is a validated instrument for identifying vaccine-hesitant parents; however, a Spanish version is not available. Utilizing the WHO framework for translating survey instruments, we used an iterative process for developing the Spanish PACV that included forward translation, expert panel review, back translation and pre-testing that utilized cognitive interviewing. We made revisions to the Spanish PACV at each step, focusing on addressing inclusivity, readability, clarity and conceptual equivalence. The expert panel was comprised of 6 Spanish-speaking medical and research professionals who worked alongside 3 study team members. Pre-testing was conducted using convenience sampling of Spanish-speaking parents (N = 35) who had a child receiving care at the residents' continuity clinic at Texas Children's Hospital. Most pre-testing participants were married (80.6%), mothers (97.1%), ≥30 years of age (88.2%) and had a high school education or less (70.6%). While the majority of participants stated the survey was easy to complete, the translation of 5 PACV items was further revised to improve interpretability. We conclude that the final Spanish PACV is conceptually equivalent and culturally appropriate for most Hispanic populations.